Restorative Masculine Integration Theory - Angelucci, Todd; Gallegos, Julian (American Journal of Men s Health, 2025)
The Restorative Masculine Integration Theory (RMIT) introduces a strengths-based, systems-oriented framework for promoting healthy masculinity through healing, leadership, and relational engagement. Developed in response to the adverse effects of masculine suppression, such as emotional disengagement, burnout, and polarity collapse, RMIT outlines a five-phase Cycle of Masculine Restoration: reclaimed masculinity, emotional safety and trust, grounded leadership, rebalanced gender polarity, and healing with cultural renewal. These stages are underpinned by core concepts including psychological safety, peer mentorship, emotional literacy, and authentic masculinity. Drawing from interdisciplinary foundations in gender studies, emotional intelligence, trauma-informed practice, polarity theory, and servant leadership, RMIT offers an adaptable framework for use across clinical, educational, organizational, and policy settings. Its alignment with the MANifest Health Theory further strengthens its applicability in men's health promotion. This manuscript elaborates the theory's conceptual development, visual model, and practical implications, while identifying future directions for empirical validation and inclusive application. RMIT advances a timely and restorative model for transforming masculine identity into a source of individual and collective resilience.
Keywords: Conceptual framework; Conceptual model; Culture theory; Empirical research; Gender identity; Grounded theory; Identity (music); Masculinity; PsycINFO; dept.nur; emotional literacy; masculinity; men’s health; peer mentorship; polarity; psychological safety; theory development; trauma-informed care